2013
DOI: 10.2119/molmed.2012.00329
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 Gates Tissue Access and Sustains Pathogenicity in Autoimmune Encephalitis

Abstract: Multiple sclerosis (MS) is a chronic progressive, demyelinating condition whose therapeutic needs are unmet, and whose pathoetiology is elusive. We report that transient receptor potential vanilloid-1 (TRPV1) expressed in a major sensory neuron subset, controls severity and progression of experimental autoimmune encephalomyelitis (EAE) in mice and likely in primary progressive MS. TRPV1 -/-B6 congenics are protected from EAE. Increased survival reflects reduced central nervous systems (CNS) infiltration, despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…1F, G). Similar to that described for other TRP channel deficiencies (18)(19)(20), TRPM8 2/2 mice exhibited a modest, albeit significant, reduction in EAE severity, which suggests a proinflammatory rather than anti-inflammatory role for this channel in the context of T cell-driven neuroinflammation ( Fig. 1G).…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…1F, G). Similar to that described for other TRP channel deficiencies (18)(19)(20), TRPM8 2/2 mice exhibited a modest, albeit significant, reduction in EAE severity, which suggests a proinflammatory rather than anti-inflammatory role for this channel in the context of T cell-driven neuroinflammation ( Fig. 1G).…”
Section: Resultssupporting
confidence: 75%
“…After inoculation, myelin-reactive CD4 + T-cell populations are expanded in the periphery and promote MS-like leukocytic infiltration and demyelination in the CNS, which leads to progressive ascending paresis and paralysis of the mouse (17). Several TRP channels have been implicated in neuroinflammation, as demonstrated by attenuated EAE progression in mice with deficiencies in TRPM4, TRPM2, and TRPV1 (18)(19)(20). In this study, we aimed to investigate the therapeutic value of icilin treatment during autoimmune-driven neuroinflammation using the EAE model, hypothesizing that an anti-inflammatory phenotype could be driven by TRPM8 channel activation.…”
mentioning
confidence: 99%
“…TRPVs are found to play an important role in immune regulation and various pathophysiological processes. TRPV1 has been attributed to the majority of immunoregulatory responses [43,[69][70][71][72][73][74][75] whereas few reports are available on TRPV4 along with other TRPs and altered immune responses in experimental immunobiological investigations [49,[76][77][78]. Together, it appears that these TRPVs are mostly involved in immunogenic responses associated with autoimmunity, inflammatory responses, and with various attributes related to disease biology.…”
Section: Discussionmentioning
confidence: 99%
“…Trpv1 -/- [14], but recently it has been reported that B6. Trpv1 -/- do not develop MOG 35-55 peptide induced EAE suggesting some immune influence [39], despite animals being obtained from the same source and using essentially the same EAE induction technique. This further highlights the inconsistency of MOG peptide-induced EAE that can sometimes occur in C57BL/6 mice [14,39].…”
Section: Discussionmentioning
confidence: 99%
“…Whether this influenced susceptibility in GPR55 knockout mice is unknown, but must be borne in mind when considering the data. However, the differences in susceptibility reported between C57BL/6.Trpv1 are unlikely to relate to genetics as the animals were from the same source, indicating that variation in disease induction can occur [14,39]. At the time of study there were no specific, high affinity GPR55 antagonists available to confirm the influence on disease course.…”
Section: Discussionmentioning
confidence: 99%